Effect of streaming on sago bark for ferulic acid production in solid state fermentation system using asperigillus flavus - Rafidah, Binti Sedup (unimas, 2015)
Ferulicacid isderived from thecinamicacid which ismostlyhigh inthecell wall ofgrass and woods. It is precursor for biovanillin production. In this study, the sago bark (powder and chips form) was used as substrate for producing ferulic acid via Solid State Fermentation by Aspergillus flavus . The effects of pre-treatment by steaming for different load of sago bark (3 g, 5 g and 7 g) were investigated. It showed that, the steaming pretreated and powder form of sago bark gives highest ferulic acid (5.42 mg/g) and feruloyl esterase (4.45 U/g) production, compared to untreated and chips form of sago bark. The data obtained that Aspergillus flavus able to utilize lignin in sago bark for generating ferulic acid. Further study should be suggested carried out on using ferulic acid forbio vanillin product.